Design, motions, capabilities, and applications of quadruped robots: a comprehensive review - Majithia, Ashish; Shah, Darshita; Dave, Jatin; Kumar, Ajay; Rathee, Sarita; Dogra, Namrata; H. M., Vishwanatha; Chiniwar, Dundesh S.; Hiremath, Shivashankarayya (Frontiers in Mechanical Engineering, 2024)
Robots are becoming integral to society and industries due to their enormous advantages. Among the various categories of mobile robots, including wheeled robot, tracked robot, and legged robots, the latter stands out as a better choice for most field applications due to their adaptability across various terrains. The purpose of this review is to study the locomotion capabilities of quadruped robots and judge their suitability for climbing applications as most unexplored applications of automation and robotics are required to climb. This review explores the locomotion capabilities of quadruped robots. It covers different aspects of quadruped robots like types of legs, leg design, gait patterns, and their mathematical formulations, and types of motions like omnidirectional motion and body sway motion. It also emphasizes its fault-tolerant gait, adaptability, and reliability. The paper also focuses on slope and stair climbing, outlining design requirements and applications. The study includes an examination of the applicability of various gaits under different conditions and the methods for increasing stability without compromising speed. Overall, the review serves as a valuable resource for future research in this field.